Establishment and application of a digital twin for vortex-induced vibration of a bridge deck section - Hao-Yang Li; You-Lin Xu; Bin Wang; Le-Dong Zhu; Xiao-Liang Meng; Guo-Qing Zhang (Engineering Applications of Computational Fluid Mechanics)
Wind tunnel tests or computational fluid dynamics (CFD) simulations of the aeroelastic model of a bridge deck section are currently used to make sure that significant vortex-induced vibration (VIV) of a long-span bridge will not occur after the bridge is put into operation. However, significant VIV still occurred in several long-span bridges in operation, indicating that the currently used wind tunnel tests and CFD simulations have some drawbacks or uncertainties. This study aims at establishing a digital twin by interacting CFD simulation with wind tunnel test for accurately and efficiently predicting the VIV response of a bridge deck. The measurement information of VIV of the deck section is collected from the wind tunnel test and fused with the CFD simulation. The optimisation for reducing uncertainties existing in wind tunnel test and CFD simulation is then carried out to make the CFD simulation as a digital twin. The digital twin is finally used to investigate the blockage effect of wind tunnel test and give an accurate and efficient prediction of VIV of the bridge deck. The flat closed-box steel deck section used in the Xiangshan Harbor cable-stayed bridge is selected as a case study. The results from the case study show that the digital twin can be established and used for an accurate and efficient prediction of VIV of the bridge deck section.